2012
DOI: 10.1007/s11999-011-2189-z
|View full text |Cite
|
Sign up to set email alerts
|

Triple Innominate Osteotomy for Legg-Calvé-Perthes Disease in Children: Does the Lateral Coverage Change With Time?

Abstract: Background Triple innominate osteotomy (TIO) is one of the modalities of surgical containment in Legg-Calvé-Perthes disease (LCPD). However, overcoverage with TIO can lead to pincer impingement. Questions/purposes We therefore asked (1) whether TIO contained the femoral head in Catterall Stages III and IV of LCPD; (2) whether the center-edge (CE) angle, acetabular roof arc angle (ARA), and Sharp's angle changed during the growing years; and (3) what percentage of patients had radiographic evidence of pincer im… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0
6

Year Published

2013
2013
2022
2022

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 27 publications
(16 citation statements)
references
References 28 publications
0
10
0
6
Order By: Relevance
“…In a retrospective review of 24 patients (mean age 9.8 years) with late onset Perthes' disease treated with shelf acetabuloplasty, Wright et al [ 23 ] recommended that the procedure deserves further evaluation in any future randomized controlled trial of the management of late onset Perthes' disease. Hosalkar et al [ 11 ] evaluated 20 triple innominate osteotomies for Perthes' disease. They concluded that it improved lateral head coverage in all cases; however, this study was conducted in children with mean age of 3.8 years.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a retrospective review of 24 patients (mean age 9.8 years) with late onset Perthes' disease treated with shelf acetabuloplasty, Wright et al [ 23 ] recommended that the procedure deserves further evaluation in any future randomized controlled trial of the management of late onset Perthes' disease. Hosalkar et al [ 11 ] evaluated 20 triple innominate osteotomies for Perthes' disease. They concluded that it improved lateral head coverage in all cases; however, this study was conducted in children with mean age of 3.8 years.…”
Section: Discussionmentioning
confidence: 99%
“…Either of these procedures does not influence the basic avascular process of head of femur. The acetabular lateral shelf procedure [ 10 ], Salter osteotomy [ 2 ], Chiari osteotomy [ 2 ], and triple osteotomy [ 11 ] are aimed at reorienting or increasing size of acetabulum and at producing more support to head of femur. However, these approaches neither reduce the pressure on the head of femur nor change the shape of the femoral head.…”
Section: Introductionmentioning
confidence: 99%
“…olacak şekilde yapılırsa, asetabular fragman daha mediyalize edilerek, kalça eklem merkezi daha fizyolojik pozisyona getirilir ve yürüme mekanizması daha iyi dü-zeltilebilir. [17,51] Steel'in yaptığı üçlü osteotomide, iskium kesisi asetabulumdan uzakta kalır (Şekil 3). Tönnis'in yöntemin-de ise kesi asetabuluma daha yakındır.…”
Section: İnnominat Osteotomiunclassified
“…Bununla beraber, aşırı örtünme Pincer tipi sıkışma sendromuna yol açabileceğinden, merkez-kenar açısı 44°'den daha fazla olacak şekilde düzeltme önerilme-mektedir. [51] …”
Section: üçLü Pelvik Osteotomiunclassified
“…The acetabular fragment must not be rotated so far as to increase the CE angle beyond 44° when a triple pelvic osteotomy is performed. 40 …”
Section: T Reatment P Lanningmentioning
confidence: 99%